Aplicação do método dos momentos para análise de um nanocircuito óptico plasmônico linear alimentado por uma sonda de abertura - SOUZA, Janilson Leão de (2018)
In this work presents a simple and efficient method of study of a linear plasmonic optical nanocircuit fed by an aperture probe. The circuit is composed by a receiver and an emitter dipole connected by a two-wire optical transmission line. The system considered was investigated in the transmission mode, where the coupling model between the aperture probe and the receiving antenna is modeled as an equivalent voltage source and as a focused Gaussian beam radiated from the aperture. The mathematical model that were utilized was the Drude-Lorentz model to represent the physical characteristics of the metal constituting the circuit and the method of moments to solve the electric field integral equation, with linear current approximation, sinusoidal basis functions and finite surface impedance. For each nanocircuits, studies were made. When the circuit were fed by a voltage source, analyzes were made utilizing near-infrared and lower optical frequencies (100-400THz). At first, we only discussed about the isolated nanodipolo transmission, where we investigated their properties and radiation absorption. Next we analyzed the impedance matching of the nanocircuit utilizing classic antenna theory to optimize the energy transfer, the results presented a variation of the induced current, planar near field distributions and reflection coefficient for different geometric parameters. In both analyzes, some results were calculated by the software Comsol. As for the case of the circuit fed by a Gaussian beam, we made a study of the impedance matching and excitation thereof to a fixed frequency with the same previous circuit calculation, differing only that the majority of results from the study shows a different geometric parameters. In both circuits, during the tests showed some conclusions about the conditions that can leads to an improvement of the impedance matching, beyond that, using the Gaussian beam excitation we made a discussion about some conditions that could allow obtaining an efficient electromagnetic coupling between the Gaussian beam, and the receiving dipole.